Precision Medicine in Cats: Novel Niemann‐Pick Type C1 Diagnosed by Whole‐Genome Sequencing. (24th February 2017) - Mauler, D.A.; Gandolfi, B.; Reinero, C.R.; O'Brien, D.P.; Spooner, J.L.; Lyons, L.A.; ,
Abstract : State‐of‐the‐art health care includes genome sequencing of the patient to identify genetic variants that contribute to either the cause of their malady or variants that can be targeted to improve treatment. The goal was to introduce state‐of‐the‐art health care to cats using genomics and a precision medicine approach. To test the feasibility of a precision medicine approach in domestic cats, a single cat that presented to the University of Missouri, Veterinary Health Center with an undiagnosed neurologic disease was whole‐genome sequenced. The DNA variants from the cat were compared to the DNA variant database produced by the 99 Lives Cat Genome Sequencing Consortium. Approximately 25× genomic coverage was produced for the cat. A predicted p.H441P missense mutation was identified in NPC1, the gene causing Niemann‐Pick type C1 on cat chromosome D3.47456793 caused by an adenine‐to‐cytosine transversion, c.1322A>C. The cat was homozygous for the variant. The variant was not identified in any other 73 domestic and 9 wild felids in the sequence database or 190 additionally genotyped cats of various breeds. The successful effort suggested precision medicine is feasible for cats and other undiagnosed cats may benefit from a genomic analysis approach. The 99 Lives DNA variant database was sufficient but would benefit from additional cat sequences. Other cats with the mutation may be identified and could be introduced as a new biomedical model for NPC1 . A genetic test could eliminate the disease variant from the population.